PERCEPTION OF TRADITIONAL UVULECTOMY AND ASSOCIATED FACTORS AMONG MOTHERS OF UNDER FIVE YEARS' CHILDREN IN SOKOTO STATE, NIGERIA - Asma'u, Adamu; Kehinde, Joseph; Mohammad, Ango; Muhammad, Bello; Muhammad, Ali; Bello, Jiya; Ilah, Garba; Omeneke, Isezuo; Omoshalewa, Ugege (European Journal of Health Sciences, 2021)
Introduction: Children are usually very vulnerable to such abuses by the traditional healers since consent is only obtained from the parents who believes in the benefits derived from traditional uvulectomy. Purpose: To assess the perception of traditional uvulectomy and associated factors among mothers of under five-year children (0-59 months) in Sokoto state. Methods: A cross sectional-study was conducted to assess the perception of traditional uvulectomy and associated factors among 320 mothers of under-five year children selected by multi stage sampling technique from 1st January-31st March 2021 in Sokoto State, Nigeria. A set of pre-tested, semi-structured interviewer- administered questionnaire was used to collect data on the research variables. Data was analysed using IBM® SPSS version 22 statistical package. Results: Majority 136(42.5%) of the respondents were between 25-34 years with a mean age of 29.9± 8.3 years. Most 304 (95.0) were Hausa's and Muslims 315 (98.4). Fulltime house wives constituted 234(73.1%) of the respondents, while those with children between1-5 were 244(76.2%). Almost two-third (65.0%) of the respondents had inappropriate perception on traditional uvulectomy (TU). Two hundred and fifteen (67.2%) of the respondents believed traditional uvulectomy should be done for under five years' children. Most (57.2%) of them perceived it is not necessary for government to come up with a law to abolish the practice of TU in the society. Majority (59.9%) of the respondents believed TU should be done for under five-year children as a tradition. Statistically significant association was observed between age, tribe and educational status of the respondents with perception of TU; (p=0.041), (p=0.002,) and (p = 0.018) respectively. Conclusion and Recommendation: This study revealed a high proportion of the respondents with inappropriate perception of traditional uvulectomy and attributed most of the childhood illness to the uvula. This underscore the need for governments at all levels to intensify action on enlightenment campaign and education of the general public through mass media and in all health facilities across the state on the dangers of TU.